The Relationship Between Medication Adherence and Quality of Life in Pulmonary Tuberculosis Patients in the Working Areas of Rengel and Plumpang Puskesmas, Tuban Regency - Karyo; Nurcahyo, Ahmad Diva; Daniel, Ahmad (LLDIKTI Wilayah 1, 2025)
Background: Based on data compiled by the Health Research and Development Agency of the Ministry of Health of the Republic of Indonesia regarding pulmonary tuberculosis (TB) cases in Indonesia, a total of 1,017,290 cases were reported in 2018 (Riskesdas, 2018). The increase in tuberculosis cases is attributed to the low adherence to medication. Low medication adherence can affect the quality of life. It has been found that the quality of life of tuberculosis patients at the Puskesmas (community health center) in Tuban Regency is still low. Therefore, research is needed to examine medication adherence in order to identify the causes of the low quality of life among tuberculosis patients in the working areas of the Rengel and Plumpang Puskesmas in Tuban Regency. Objective: To determine the relationship between medication adherence and the quality of life of tuberculosis patients in Tuban Regency. Method: This study used a Cross-Sectional research design. The sampling technique employed was simple random sampling. A total of 94 respondents participated in this study. Data collection was carried out by distributing questionnaires directly while adhering to health protocols. Results: The study results indicated that tuberculosis patients in Tuban Regency exhibited moderate self-care, with 30 patients (31.91%) reporting frequent self-care, and 38 patients (40.43%) reporting an average quality of life. The Spearman correlation test, conducted using SPSS 25 for Windows, showed a significance value of p = 0.000, indicating that the smaller the p-value, the more significant the results. Since ? < ? (0.000 < 0.05), and the correlation coefficient (r) was 0.671, which indicates a strong correlation. Conclusion: The quality of life of tuberculosis patients is not only influenced by medication adherence but also by other factors that affect the implementation of medication adherence.